Contemporary Methodological Perspectives in Educational Research on 'Teachers' practice': Assumptions and Shortcomings for 'Effective Practices'. (July 2019) - Penalva, José
In the context of the major influence that 'effectiveness' is having internationally, paper studies the contemporary methodological perspectives in educational research when considering teachers' practice. It shows that current trends can be boiled down to: (1) naturalistic methodology, (2) descriptive methodology, and (3) the nonmethodological solution. It states two main conclusions: first, there is a neat continuity with traditional methodologies, which were in decline long ago; second, contemporary perspectives in educational research fail to provide a consistent methodological model for 'effective practices'. The author finally draws some conclusions and makes some suggestions for the further development of methodology in educational research and teachers' practice. This study is noteworthy for teachers' practice, collaborations and partnerships, and also for the relationship amongst research/practice/policy, which is at the core of the implementation of educational systems.